Assessment of the sustainability of fibre-reinforced concrete by considering both environmental and mechanical properties - Soltanzadeh, Fatemeh (2022)
The environmental consequences of human activities, e.g., the depletion of non-renewable fuel resources, consumption of natural raw materials, and release of huge amounts of CO2 into the atmosphere, resulted in new challenges in materials engineering. Based on these challenges, building materials must fulfil not only mechanical performance criteria, but also produce the least environmental impact accompanied by their production. In the present study, the possibility of employing scrap tire recycled steel fibres (RSF) as a substitution to industrial steel fibres (ISF) for developing more sustainable fibre-reinforced concretes was explored by adopting a life-cycle approach, integrated both environmental and mechanical properties. Four different fibre-reinforced self-compacting concretes–FRSCCs–were tailored by means of replacing the ISFs partially/totally (i.e., 0%, 50%, 67%, 100% by mass of) with the recycled ones. The effect of applying various dosages of RSFs on mechanical behavior of FRSCC–namely compressive, flexural, and splitting tensile responses–were evaluated experimentally. The environmental impacts associated with the production of each FRSCC were also assessed through life-cycle analysis. The potentiality of the RSFs to be used as concrete reinforcement with a comparable mechanical performance to that of ISF-reinforced concrete and lower environmental footprint was evaluated through a consolidated environmental and mechanical index (EM). In this study, using RSFs instead of industrial fibres for developing FRSCC has provided up to 37% higher EM index. The results confirmed the promising prospects for the application of RSFs in developing more eco-efficient and sustainable reinforced concrete.